A Review on Nuclear Energy (International Journal of Innovative Research in Engineering & Management, 2021)
Sustainability is described as an environmental strategy that is  ideally suited for eco-systems and capable of successfully and  continuously managing a cycle. In every aspect, the key to the  humanity race's long-term survival is sustainability. Due to  recent resource depletion and worries about climate change,  many people are considering the benefits and dangers of  nuclear energy as a viable option. Nuclear energy's  advantages, such as no greenhouse gas emissions and a large  amount of low-cost electricity, are severely restricted by the  risk of fatal accidents and the long-term disposal of  radioactive waste. This article highlights the advantages and  dangers of nuclear power for a sustainable energy demand  since nuclear power is a matter of balancing gain and risk.  Robotic systems are an excellent solution to some of these  issues since they remove the need for humans to visit these  places while also providing data on their health that would  otherwise be inaccessible. However, each robot's requirements  are sometimes very different, or even the most robust  platforms may encounter considerable challenges owing to the  unique characteristics of a particularly challenging  environment. However, such improvements may be both  costly and time-consuming to implement. Sustainability are  all words that come to mind while thinking about climate  change. Sustainability are all words that come to mind while  thinking about climate change.
Keywords: Climate Change; Energy Intensity; Effects; Nuclear Energy; Radioactivity